2017
DOI: 10.1186/s12864-017-4290-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic insight into fruit set of cucumber (Cucumis sativus L.) suggests the cues of hormone-independent parthenocarpy

Abstract: BackgroundParthenocarpy is an excellent agronomic trait that enables crops to set fruit in the absence of pollination and fertilization, and therefore to produce seedless fruit. Although parthenocarpy is widely recognized as a hormone-dependent process, hormone-insensitive parthenocarpy can also be observed in cucumber; however, its mechanism is poorly understood. To improve the global understanding of parthenocarpy and address the hormone-insensitive parthenocarpy shown in cucumber, we conducted a physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 80 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…Parthenocarpy can overcome these problems by converting the ovary into a developing fruit without pollination and exogenous hormone application, thereby producing seedless fruit. Currently, for highly desired agronomic traits, many vegetable crops, such as tomato ( Gorguet et al, 2005 , 2008 ; Takisawa et al, 2017 , 2020 ), cucumber ( Wu et al, 2016 ; Li et al, 2017 ), and eggplant ( Du et al, 2016 ; Chen et al, 2017 ) can naturally produce parthenocarpic fruit. The use of parthenocarpic cultivars is considered to be the most cost-effective solution for a stable fruit set under suboptimal environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Parthenocarpy can overcome these problems by converting the ovary into a developing fruit without pollination and exogenous hormone application, thereby producing seedless fruit. Currently, for highly desired agronomic traits, many vegetable crops, such as tomato ( Gorguet et al, 2005 , 2008 ; Takisawa et al, 2017 , 2020 ), cucumber ( Wu et al, 2016 ; Li et al, 2017 ), and eggplant ( Du et al, 2016 ; Chen et al, 2017 ) can naturally produce parthenocarpic fruit. The use of parthenocarpic cultivars is considered to be the most cost-effective solution for a stable fruit set under suboptimal environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A proteomic study of scion-rootstock graft revealed 50 proteins that were differentially expressed and that those proteins were involved in a wide range of functions, including photosynthesis, carbohydrate metabolism, energy metabolism, and protein metabolism [39]. Cluster analysis showed that 41 parthenocarpy-related, differentially expressed proteins were screened in cytokinin-induced and naturally occurring parthenocarpic fruits, which confirmed that hormone-insensitive proteins can manipulate the mechanism of hormone-independent parthenocarpy [40]. The application of a plant growth-promoting Trichoderma strain (T. longibrachiatum "H9") to cucumber roots resulted in the upregulation of genes and proteins that were mainly involved in defense/stress processes, secondary metabolism, phytohormone synthesis, and signal transduction [41].…”
Section: Proteome Research Of Cucumbermentioning
confidence: 85%
“…Consistent with early observations showing that inhibitors of auxin transport that block movement of auxin out of the ovary can promote parthenocarpy [ 41 ], parthenocarpic cucumbers exhibited decreased transcription of the auxin receptor and signal transport genes CsTIR1 and CsAFB2 [ 42 ]. Interestingly, hormone-insensitive parthenocarpy also has been observed in certain lines of cucumber, possibly resulting from expression of proteins that showed hormone-insensitive patterns in both ovaries and seedlings [ 43 ].…”
Section: Fruit Development Size and Shapementioning
confidence: 99%
“…As is the case for fruit set following pollination, import of sugars is critical for parthenocarpic fruit growth. Increased sugar transport was associated with increased expression of auxin and cytokinin signaling genes suggesting interplay among sugars and plant hormones [ 44 ], and a higher rate of cell division in parthenocarpic fruit was associated with higher carbohydrate metabolism [ 43 ]. In some genetically parthenocarpic lines, especially European greenhouse types, parthenocarpy has been associated with weaker first fruit inhibition (e.g., [ 45 ]), potentially providing a yield advantage.…”
Section: Fruit Development Size and Shapementioning
confidence: 99%